Does Gold Retain its Hedge and Safe Haven Role for Energy Sector Indices During COVID-19 Pandemic? A Crossquantilogram Approach - Manohar, Jambotkar Mrunali; Raju, Guntur Anjana (International Journal of Energy Economics and Policy, 2020)
The Outbreak of the COVID-19 Pandemic has caused unprecedented risk and uncertainty in the global financial markets. The shattered investor's faith in the Global Financial system has stimulated the need to explore safe haven assets to mitigate risk and safeguard wealth during such turmoil. Therefore, this paper addresses the widely mooted hedge and safe haven property of gold against extreme downturns in the stock market energy sector indices during COVID-19 distress. The sample countries considered comprises of the USA, Saudi Arabia, UAE, Russia, Canada, India and China being strategically linked to gold and oil commodities. Splitting the sample period into Pre-COVID period from 30th June 2019 to 30th December 2019 and During-COVID period from 31st December 2019 to 30th June 2020 the study employs bivariate cross-quantilogram of (Han, et al., 2016) to examine directional predictability in quantiles between gold and energy sector indices. The results confirm the inability of gold to showcase its pronounced hedge and safe haven role before the COVID-19 crises. Specifically, Countries such as Saudi Arabia, Russia and Canada show a significant negative predictability from energy sector indices to gold thereby indicating its safe haven role during COVID-19 crises. Keywords: Gold, Safe Haven, COVID-19, Cross-quantilogram, Energy sector Indices. JEL Classifications: G01, G11, G15, Q40 DOI: https://doi.org/10.32479/ijeep.10294